2015
DOI: 10.1292/jvms.14-0380
|View full text |Cite
|
Sign up to set email alerts
|

Serotype- and virulence-associated gene profile of <i>Streptococcus suis</i> isolates from pig carcasses in Chiang Mai Province, Northern Thailand

Abstract: In this present study, the serotype of 40 Streptococcus suis isolates from submaxillary glands of pig carcasses sold in wet markets in Chiang Mai Province, northern Thailand, was investigated. Eleven serotypes, including types 2, 3, 4, 5, 7, 8, 9, 17, 21, 22 and 31, were found in the isolates by a Multiplex PCR combined with serum agglutination. Of the eleven serotypes present, type 3 was the most prevalent, while types 2, 4, 5 and 21 were of primary interest due to their human isolate serotype. The mrp+/epf −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
4
8
1
Order By: Relevance
“…Two studies were carried out in Chiang Mai, northern Thailand. The first study showed that in samples from the submaxillary gland of pig carcasses, serotype 3 was the most prevalent (17.5%), followed by serotypes 2 (12.5%) and 4 (10%) [26]. In the second study, Padungtod et al reported that serotypes 2 (43%) and 7 (14.3%) were more prevalent in healthy pigs than diseased pigs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were carried out in Chiang Mai, northern Thailand. The first study showed that in samples from the submaxillary gland of pig carcasses, serotype 3 was the most prevalent (17.5%), followed by serotypes 2 (12.5%) and 4 (10%) [26]. In the second study, Padungtod et al reported that serotypes 2 (43%) and 7 (14.3%) were more prevalent in healthy pigs than diseased pigs [27].…”
Section: Discussionmentioning
confidence: 99%
“…As thiol-activated hemolysin may be associated with the ability of the bacteria to penetrate into deeper tissues, isolates from the lungs might be less capable of penetrating different organs and is not considered a primary agent of pneumonia [6, 22]. The virulence-associated gene distribution patterns of Korean isolates were similar to those of North American isolates in 2003–2005 and Northern Thailand isolates in 2001–2002 [7, 43]: epf − / mrp + / sly − (35.4%) was the most prevalent, followed by epf − / mrp − / sly + (20.0%) and epf − / mrp + / sly + (16.3%). Therefore, overall, the virulence-associated gene distribution in the present study can be characterized by the high prevalence of mrp and low epf prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been suggested to contribute to the virulence of S. suis ; however, most of the studies conducted thus far have focused on identification of the following three factors: muraminidase-released protein (MRP), extracellular protein factor (EF) and suilysin (SLY) [7, 33, 43]. MRP and EF are suspected to be associated with virulence in certain strains of S. suis [42, 45].…”
mentioning
confidence: 99%
“…Thirty-seven percent of the isolates was nontypable by multiplex PCR ( Thongkamkoon et al, 2017 ). Another study from Northern Thailand (Chiang Mai Province) found mostly serotype 3 isolates in submaxillary glands of pig carcasses sold in wet markets ( Wongsawan et al, 2015 ). A further study investigated samples from asymptomatic pigs from central Thailand and found mainly serotype 16 strains ( Meekhanon et al, 2017 ).…”
Section: Diversity Of S Suismentioning
confidence: 99%